Climate matching with the climatchR R package. (November 2022) - Erickson, Richard A.; Engelstad, Peder S.; Jarnevich, Catherine S.; Sofaer, Helen R.; Daniel, Wesley M.
Abstract: Climate matching allows comparisons of climatic conditions between different locations to understand location and species range climatic suitability. The approach may be used as part of horizon scanning exercises such as those conducted for invasive species. We implemented the CLIMATCH algorithm into an R package, climatchR . The package allows automated and scripted climate matching exercises across all steps from downloading data to summarizing species climate matches. We also show how climatchR may be used with high-throughput computing to process many species. For example, we were able to calculate climate scores for over 8, 000 species in less than 3 days using this package. This automation allows high-throughput processing of species data, a new development for improving the efficiency and speed of climate matching and horizon scanning. Highlights: climatchR allows for scripted and high-throughput climate matching with the R language. climatchR works with a wide range of taxa including birds, mammals, fishes, reptiles, and amphibians. The package may be used to identify potential areas for new species invasion (e.g., how well does the climate in a species established range match possible target ranges?). climatchR readily integrates with high-throughput computing methods, specifically HTCondor.